The Effect of Provenance, Plant Spacing and Cutting Interval on Leaf Biomass Yield of Moringa Oleifera Lam. Issue 1 (5th July 2019) - Gadzirayi, C. T.; Kubiku, F.; Mupangwa, J.; Masamha, B.; Mujuru, L.
ABSTRACT: Two provenances of Moringa oleifera Lam., Malawi and Mutoko, were evaluated to determine the effect of plant spacing and cutting interval on the leaf biomass yield for fodder production. A split-split plot experimental design was set up with provenance as the main plot factor, plant spacing as sub-plot factor and cutting interval as sub-sub plot factor. The provenances were tested at two plant spacings of 15 cm × 15 cm and 20 cm × 20 cm, and two cutting intervals of 60 days and 75 days. Results showed that 90 days after planting, at 20 cm × 20 cm spacing, Malawi provenance plants had a higher ( P < 0.05) leaf dry matter yield than Mutoko plants. A cutting interval of 60 days had a higher ( P < 0.05) leaf dry matter yield for the two provenances than a 75 day cutting interval. Both provenances can be recommended for agroforestry because their leaf biomass yields were not significantly different at all subsequent cutting intervals of 60 and 75 days.